If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9x + 2)(x + -3) = 0 Reorder the terms: (2 + 9x)(x + -3) = 0 Reorder the terms: (2 + 9x)(-3 + x) = 0 Multiply (2 + 9x) * (-3 + x) (2(-3 + x) + 9x * (-3 + x)) = 0 ((-3 * 2 + x * 2) + 9x * (-3 + x)) = 0 ((-6 + 2x) + 9x * (-3 + x)) = 0 (-6 + 2x + (-3 * 9x + x * 9x)) = 0 (-6 + 2x + (-27x + 9x2)) = 0 Combine like terms: 2x + -27x = -25x (-6 + -25x + 9x2) = 0 Solving -6 + -25x + 9x2 = 0 Solving for variable 'x'. Factor a trinomial. (-2 + -9x)(3 + -1x) = 0Subproblem 1
Set the factor '(-2 + -9x)' equal to zero and attempt to solve: Simplifying -2 + -9x = 0 Solving -2 + -9x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -9x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -9x = 0 + 2 -9x = 0 + 2 Combine like terms: 0 + 2 = 2 -9x = 2 Divide each side by '-9'. x = -0.2222222222 Simplifying x = -0.2222222222Subproblem 2
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Solution
x = {-0.2222222222, 3}
| 5x-123=87+12x | | 4n(8+3)=132 | | (4x-7)(x+4)= | | .80=ln(y) | | 10c-9c=6 | | z^2+12z=20 | | -5(x-2)-3x=2-(-8+3x) | | 3p-2= | | 7x-(3x+11)=-6(5-3x) | | -x+64=5x-14 | | 9t-3t-5t-2t-4t=18 | | 25x^2-30x+21=0 | | 8x-13=35 | | 4y^4-37y^2+9=0 | | 6r+3=3r-27 | | C=5x+770 | | 7c*2p+3-8=6p+29 | | (7x+3)=2 | | 16s+4s=20 | | 9n-37=71 | | 3h-h=10 | | 2(x+9)=20 | | 9m-6m=6 | | 10w-4w=18 | | (x+3y)(3x+y)= | | (1+2w)*w*2w=40 | | -60x^3+144x= | | c/4+85=99 | | 4x+1=6-x | | -4+6s+7m-4s-4m-6= | | 2(13-4x)-9(x+6)= | | 49x^2-91+42=0 |